Association Between Parental Attendance at Early Adolescence’s Parent–Teacher Conferences and Their Children’s Performance in Standardized Exams for High School and College Entrance - Sydney L. Fu; Sean O. Fu; Rebecca Y. Chen; Earl Fu; Martin M. Fu; Tony Szu-Hsien Lee; Hsun-Yu Chan (Education Sciences)
Adolescents’ performance in high-stakes standardized examinations plays a pivotal role in shaping their educational trajectories. This longitudinal study investigated whether parental attendance at parent–teacher conferences (PTCs) during early adolescence is associated with students’ performance in standardized examinations required for high school and college entrance. Drawing on data from the Taiwan Youth Project, we analyzed responses from 1294 ninth-grade students and 524 twelfth-grade students with available exam results. Parental participation in PTCs was recorded in both seventh and eighth grades, along with two other types of school-based involvement and covariates, such as parental education level, household income, students’ birth order, prior academic rank, peer relationships, parental support, and parental expectations. Hierarchical linear modeling was employed to control for individual and school-level variables. The results showed that parental attendance at PTCs in eighth grade was associated with higher scores on high school entrance exams in ninth grade. Furthermore, attending PTCs in both seventh and eighth grades was significantly associated with better performance in college entrance exams in twelfth grade (β = 3.02, p < 0.01). These findings suggest that sustained parental engagement in PTCs contributes to improved academic performance in adolescence. Policies that promote equitable and continued parent–teacher collaboration may support long-term student success.